KARAKTERISTIK GLIKOGEN TEMILOK (Bactronophorus thoracites) BERMUTU RENDAH SEBAGAI KO-PRESIPITAN ASAM DEOKSIRIBONUKLEAT - DENNY SYAPUTRA; BUSTAMI IBRAHIM; PUTUT TJAHYO WIDODO (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2012)
Temilok (Bactronophorus thoracites) is one of Teredinidae or family of wood-borer shellfish in fact have a fairly high polysaccharide content, particularly interesting source of glycogen. The object of this experiment is to investigate the impurity contents (nitrogenous compounds and nucleic acids) of extracted glycogen from low quality of temilok based on Nicoletti and Baiocchi glycogen polysaccharide extraction patent method by comprising boiling the whole tissue in an aqueous solution of 40% potassium hydroxide (KOH) and treated with 12% cationic resin Amberlite IR-120 carried out for 16 hours under stirring at room temperature, and the ability of the extracted glycogen as co-precipitant in the precipitation of deoxyribonucleic acid (DNA) of human femur. Nitrogen and nucleic acid content of extracted glycogen were spectrophotometrically measured at 260 nm, 280 nm and 320 nm. Extracted glycogen samples was characterized by determining the glucose content quantitatively using phenol-sulphate method which measured spectrophotometrically at 490 nm . The nitrogen content of extracted glycogen was about 0,8%, yield about 6,5% glycogen characterized as the lowest nucleic acids content i.e 0,07 mg/mL. In order to asses the ability of the extracted glycogen as carrier or co-precipitant of low copy number DNA, we added 20 µL the 2% solution of the extracted glycogen into first step of femur DNA procedure of precipitation. Results revealed that by adding the extracted glycogen solutions, the yield of DNA were not significantly affected at the level of 0,05 though the yield of DNA decreased against blanko about 0,005 ng/µL of 0,0401 ng/µL